2019
DOI: 10.1021/acs.jmedchem.8b01508
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivatable Prodrug of Doxazolidine Targeting Exosomes

Abstract: Natural lipid nanocarriers, exosomes, carry cell-signaling materials such as DNA and RNA for intercellular communications. Exosomes derived from cancer cells contribute to the progression and metastasis of cancer cells by transferring oncogenic signaling molecules to neighboring and remote premetastatic sites. Therefore, applying the unique properties of exosomes for cancer therapy has been expected in science, medicine, and drug discovery fields. Herein, we report that an exosome-targeting prodrug system, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The process was monitored by UV–vis spectrometry and the photocleavage rate determined by UPLC (see Supporting Figure S1 ). Based on this analysis, the photocleavage quantum yield was calculated as 4.4%, indicating that the photocleavage efficiency of our photoactive scaffold lies in the same range as the one of comparable examples of NVOC-photocaged carboxylic acids, including methyl-substituted ones [ 47 , 48 , 49 ]. Still, it has to be noted that the quantum yield in aqueous medium possibly differs from the one in aprotic organic solvent, since—at least for photocaged alcohols—the cleavage mechanism is based on proton transfer and is known to be affected by changes in pH and solvent.…”
Section: Resultsmentioning
confidence: 80%
“…The process was monitored by UV–vis spectrometry and the photocleavage rate determined by UPLC (see Supporting Figure S1 ). Based on this analysis, the photocleavage quantum yield was calculated as 4.4%, indicating that the photocleavage efficiency of our photoactive scaffold lies in the same range as the one of comparable examples of NVOC-photocaged carboxylic acids, including methyl-substituted ones [ 47 , 48 , 49 ]. Still, it has to be noted that the quantum yield in aqueous medium possibly differs from the one in aprotic organic solvent, since—at least for photocaged alcohols—the cleavage mechanism is based on proton transfer and is known to be affected by changes in pH and solvent.…”
Section: Resultsmentioning
confidence: 80%
“…The phototoxicity of numerous pharmaceutical materials is a major therapeutic concern that can conspicuously constrain their clinical applications [14][15][16][17][18]. Several approaches have been recently developed toward reducing the impact of such undesired side effects, including photocaging [19][20][21][22][23][24]. Recently, the importance of the incorporation of photocaging groups into photoactive pharmaceutical materials has been increasingly recognized as an effectual approach toward reducing the phototoxicity of a wide spectrum of photoactive drugs [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As such, several studies have been recently reported concerning the photocaging of materials of biological and pharmaceutical importance, such as the antimelanoma agent vemurafenib [20], anticancer drug doxazolidine [21], anticancer kinase inhibitor imatinib [22], small-molecule tubulin inhibitor [23], and photocaged materials for homeostasis [24]. Various types of photolabile-protecting groups (PPGs) have been developed and utilized in these works to afford the photocaged prodrugs of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…off-target effects of systemically administered anticancer drugs heavily constrained their efficacy and tolerability. The photocaging concept has been used in the delivery of drugs across membranes; it reduces off-target effects, as exemplified by photoactivatable prodrug (97) of the anti-melanoma agent vemurafenib (96), caged RET kinase inhibitor 99, 113 photoactivatable caged prodrugs (101 and 102) of imatinib (100), 114 photocontrolled HDAC inhibitors 103,104 115,116 and 106, a photoactivatable prodrug of doxazolidine (105) targeting exosomes (Figure 14) 117. Meanwhile, a number of PPGs have been exploited for this purpose, including p-nitrobenzyl, 4,5-dimethoxy-2-nitrobenzyl, 7-diethylaminocoumarin-4-ylmethyl, and 6-bromo-7-hydroxycoumarine-4-ylmethyl.…”
mentioning
confidence: 99%